Outcomes of Recipients With Pancreas Transplant Alone Who Develop End‐Stage Renal Disease. Issue 2 (2nd November 2015) - Singh, S. K.; Kim, S. J.; Smail, N.; Schiff, J.; Paraskevas, S.; Cantarovich, M.
Abstract : Recipients of pancreas transplant alone (PTA) may be at increased risk for developing end‐stage renal disease (ESRD). The survival experience of PTA recipients developing ESRD has not been described. Furthermore, the relative survival of these patients as compared to diabetics on chronic dialysis is unknown. We studied all adult PTA recipients from January 1, 1990 to September 1, 2008 using the Scientific Registry of Transplant Recipients. Each PTA recipient developing ESRD was matched to 10 diabetics on chronic dialysis from the United States Renal Data System. Cox proportional hazards models were fitted to determine the relation between ESRD and mortality among PTA recipients, and the relation between PTA and mortality among diabetics on chronic dialysis. There were 1597 PTA recipients in the study, of which 207 developed ESRD. Those with ESRD had a threefold increase in mortality versus those without (adjusted hazard ratio 3.28 [95% confidence interval: 2.27, 4.76]). There was no significant difference in the risk of death among PTA recipients with ESRD versus diabetics on dialysis. PTA recipients developing ESRD are three times more likely to die than PTA recipients without ESRD; however, the risk of death in these patients was similar to diabetics on chronic dialysis without PTA.